Bioactive, nanostructured Si‐substituted hydroxyapatite coatings on titanium prepared by pulsed laser deposition. Issue 8 (30th December 2014) - Rau, Julietta V.; Cacciotti, Ilaria; Laureti, Sara; Fosca, Marco; Varvaro, Gaspare; Latini, Alessandro
Abstract Aims: The aim of this work was to deposit silicon‐substituted hydroxyapatite (Si‐HAp) coatings on titanium for biomedical applications, since it is known that Si‐HAp is able to promote osteoblastic cells activity, resulting in the enhanced bone ingrowth. Materials and Methods: Pulsed laser deposition (PLD) method was used for coatings preparation. For depositions, Si‐HAp targets (1.4 wt % of Si), made up from nanopowders synthesized by wet method, were used. Results: Microstructural and mechanical properties of the produced coatings, as a function of substrate temperature, were investigated by scanning electron and atomic force microscopies, X‐ray diffraction, Fourier transform infrared spectroscopy, and Vickers microhardness. In the temperature range of 400–600°C, 1.4–1.5 µm thick Si‐HAp films, presenting composition similar to that of the used target, were deposited. The prepared coatings were dense, crystalline, and nanostructured, characterized by nanotopography of surface and enhanced hardness. Whereas the substrate temperature of 750°C was too high and led to the HAp decomposition. Moreover, the bioactivity of coatings was evaluated by in vitro tests in an osteoblastic/osteoclastic culture medium (α‐Modified Eagle's Medium). Conclusions: The prepared bioactive Si‐HAp coatings could be considered for applications in orthopedics and dentistry to improve the osteointegration of bone implants. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1621–1631, 2015.